HUBUNGAN PHBS DENGAN KEJADIAN DIARE PADA BALITA USIA 3-5 DI DESA PENYASAWAN TAHUN 2022 - Gustiana, Etri; Alini, Alini; Zurrahmi, Zurrahmi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Environmental-based diseases still dominate health problems in developing countries. Diarrhea is one of the environmental-based diseases that causes death in the world. The aim of this research is to determine the relationship between PHBS and the incidence of diarrhea in toddlers aged 3-5 years in Penyasawan Village in 2022. This type of research is analytical with a cross sectional design. The population in the study were all mothers with toddlers in Penyasawan Village, totaling 517 people with a sample of 84 people. The sampling technique uses simple random sampling. The data collection tool uses a questionnaire. The data analysis used in this research is univariate and bivariate analysis. The research results showed that there is a significant relationship between PHBS and the incidence of diarrhea in toddlers in Penyasawan Village in 2022 with a p value of 0.003. It is hoped that parents who have toddlers will increase their knowledge about preventing diarrhea at home, as well as further improve clean and healthy living behavior. especially taking steps to prevent diarrhea, such as washing hands before eating with soap.